Particle size-dependent biomolecular footprints of interactive microplastics in maize. (15th May 2021) - Pehlivan, Necla; Gedik, Kenan
Abstract: The world is dealing with the mismanaged plastic waste found even in the Arctic. The crisis is being tried to solve with the plastivor bugs or bio-plastics, and the marine pollution profiles become priority however, putative phytotoxicity on terrestrial farming have not received significant attention. Hence, morpho-physiological and molecular response in maize seedlings exposed to the most prevalent microplastic (MP) types (PP, PET, PVC, PS, PE) differing in their particle size (75–150 μm and 150–212 μm) and combinations (PP + PET + PVC + PS + PE mix) was analyzed here for a predictive holistic model. While POD1 regulating the oxidative defense showed a slight down-regulation, HSP1 abundance quantified in the 75–150 μm MP lead a significant up-regulation particularly for PET (2.2 fold) PVC (3.3 fold), and the MP mix (6.4 fold). Biochemical imbalance detected at lower sized (75–150 μm) MPs in particular at the MP mix, involved the cell membrane instability, lesser photosynthetic pigments and a conjectural restraint in the photosynthetic capacity along with the accumulated endogenous H2 O2 proved that the bigger the particle size the better the cells restore the damage under MP-caused xenobiotic stress. The determination of the impacts of MP pollution in in-vitro agricultural models might guide the development of policies in this direction and help ensure agricultural security by predicting the possible pollution damage. Graphical abstract: Image 1 Highlights: The physical nature and size of the MPs is of vast significance in plant stress response network. Smaller MPs particle size leads to potential redox deregulation. Larger MPs might help economizing the water budget. The mix, PET and PS left the most hazardous signatures. POD1 and HSP1 are hub elements in transduction of MPs caused ROS into gene transcript expression. Abstract : The MP mix, PET, and PS left the most hazardous signatures on seedlings via ROS triggered by mechanical and/or xenobiotic damage.